Numerical simulation of Telekom Malaysia (TM) server farm thermal transport phenomena using ansys fluent / Mohd Aswad Othman - Mohd Aswad , Othman (2019)
A server farm or server cluster is a computer server collection maintained by an organization to provide server functionality far beyond a single machine's capability. Since the servers are stored in close proximity to one another, an efficient cooling is a must. Thus this research aims to simulate the thermal transport phenomena of a server farm managed by Telekom Malaysia(TM) under the TM city project. To simulate the thermal transport phenomena, Ansys-Fluent was used. Using Ansys Fluent, temperature distribution across the server farm had been determined. It is found that using original setup, cooling air distributed at the front of the server racks can reach a maximum of 27°C and almost exceeds the maximum recommended temperatures as per guidelines released by ASHRAE. This is mainly due to hot air recirculation from the back of the server racks back into the cold aisles. To eliminate this problem, cold aisle containment system is suggested to be installed. Simulation on the server farm equipped with cold aisle containment system shows that the maximum temperature in front of the server racks drops to 25°C and becomes more evenly distributed. The cold aisle containment system also managed to eliminate hot air recirculation from the back of the server racks.